Improving Cloud Data Storage Using Data Partition and Recovery (International Journal of Engineering and Computer Science, 2015)
Cloud storage system allows storing of data in to thecloud server efficiently and makes the user to work with thedata without any problem, trouble of the resources. Also theCloud storage permits users to remotely store their data andenjoy it on _demand high quality cloud applications withoutthe burden of local hardware and software management. Inexisting system data are stored in the cloud using dynamicdata operation with computation which makes the user need tomake a copy of data for further updating and verification ofthe data loss unfortunately.